Comparative review of human and canine osteosarcoma: morphology, epidemiology, prognosis, treatment and genetics - Simpson, Siobhan; Dunning, Mark D.; de Brot, Simone; Grau-Roma, Llorenc; Mongan, Nigel P.; Rutland, Catrin S. (BioMed Central, 2017)
Osteosarcoma (OSA) is a rare cancer in people. However OSA incidence rates in dogs are 27 times higher than in people. Prognosis in both species is poor, with five year osteosarcoma survival rates in people not having improved in decades. For dogs, one year survival rates are only around ~45%. Improved and novel treatment regimens are urgently required to improve survival in both humans and dogs with OSA. Utilising information from genetic studies could assist in this in both species, with the higher incidence rates in dogs contributing to the dog population being a good model of human disease. This review compares the clinical characteristics, gross morphology and histopathology, aetiology, epidemiology, and genetics of canine and human osteosarcoma. Finally, the current position of canine osteosarcoma genetic research is discussed and areas for additional work within the canine population are identified.